Multisystem Radiologic Manifestations of Erdheim-Chester Disease - Umairullah Lodhi; Uzair Sarmast; Saadullah Khan; Kavitha Yaddanapudi (Case Reports in Radiology)
Erdheim-Chester Disease is a rare form of multiorgan non-Langerhans’ cell histiocytosis that affects individuals between the ages of 50 and 70 with an equal distribution among males and females. It is associated with significant morbidity and mortality that is mostly due to infiltration of critical organs. Some of the sites that Erdheim-Chester Disease affects include the skeletal system, central nervous system, cardiovascular system, lungs, kidneys (retroperitoneum), and skin. The most common presenting symptom of Erdheim-Chester Disease is bone pain although a large majority of patients are diagnosed incidentally during a workup for a different disease process. Diagnosing Erdheim-Chester Disease is challenging due its rarity and mimicry to other infiltrative processes. Therefore, a multimodality diagnostic approach is employed with imaging being at the forefront. As of date, a comprehensive radiologic review of the manifestations of Erdheim-Chester Disease has rarely been reported. Here we present radiologic findings of an individual suffering from Erdheim-Chester Disease.